The Influence of Mandatory Vs. Non-Mandatory Influenza Vaccination Policies on Workplace Absenteeism During Respiratory Virus Season. (4th October 2017) - Simberkoff, Michael S; Frederick, John; Brown, Alexandria; Cummings, Derek; Gaydos, Charlotte; Gibert, Cynthia; Gorse, Geoffrey; Nyquist, Ann-Christine; Perl, Trish; Price, Connie; Radonovich, Lewis J; Reich, Nicholas; et al.
Abstract: Background: We analyzed data from health care personnel (HCP) participating in the multicenter, cluster randomized Respiratory Protection Effectiveness Clinical Trial (ResPECT) obtained over three viral respiratory (influenza) illness seasons (2012–2015) at three university health systems where influenza vaccination was mandated, and four Veterans Affairs (VA) health systems where it was encouraged but not mandated, to determine the incidence and duration of symptomatic influenza like illness (SILI) associated absenteeism. Methods: Participants reported SILI daily, vaccination status, and days absent from work due to SILI weekly throughout a 12 week period during the peak viral respiratory illness season each year. Adjusted effects of vaccination and other modulating factors on absenteeism rates were estimated using multivariable regression models. Results: Overall 97.1%, 96.3%, and 92.1% of participants reported being vaccinated during each of the three study years where the vaccine was mandated, while 67.9%, 63.3%, and 60.4% reported vaccination at sites where it was encouraged but not mandated. The percent of HCP claiming any sick days at mandatory sites was estimated to be 5.9% lower than at non-mandatory sites (95% CI, -12.5, -1.4; P = 0.02). Among HCP who reported at least one sick day, the mean number of symptomatic sick days at mandatory sites was 0.74 lower than at non-mandatory sites (95% CI, -1.37, -0.37, P < 0.01). After adjusting for possible confounding factors (e.g., season, vaccination statues, mandatory or non-mandatory vaccination site, age, children at home) the relative rate of sick days taken by vaccinated compared with unvaccinated subjects was reduced in the entire cohort of HCP and in the vaccinated compared with unvaccinated subset of HCP from non-mandatory sites (see Figure). Conclusion: We conclude that influenza vaccination rates are increased and SILI-related absenteeism is decreased at sites where influenza vaccination is mandated and that this should be one of the factors taken into consideration when healthcare facilities make decisions about influenza vaccination policies. Disclosures: All authors: No reported disclosures.